Fay, C.R. - White, Linda, 1950- (2010)
Draft of four chapters of 'Life and Labour in Newfoundland', a series of lectures based on two tours of Newfoundland and Labrador in 1952 and 1953 and delivered at Memorial University in 1953. Published by University of Toronto Press, 1956.